Novel Insights Into Illness Progression and Risk Profiles for Mortality in Non-survivors of COVID-19 - Shao, Liang; Li, Xinyi; Zhou, Yi; Yu, Yalan; Liu, Yanan; Liu, Minghui; Zhang, Ruixian; Zhang, Haojian; Wang, Xinghuan; Zhou, Fuling (Frontiers in Medicine, 2020)
Background. The outbreak of COVID-19 has attracted the attention of the whole world. Our study aims to describe illness progression and risk profiles for mortality in non-survivors. Methods. We retrospectively analyzed 155 patients with COVID-19 in Wuhan and focused on eighteen non-survivors among them. Briefly, we compared the dynamic profile of biochemical and immune parameters and drew an epidemiological and clinical picture of disease progression from disease onset to death in non-survivors. The survival status of the cohort was indicated by Kaplan-Meier curve. Results. Of the non-survivors, the median age was 73.5 years and the proportion of males was 72.2%. Five and thirteen patients were hospital-acquired and community-acquired infection of SARS-CoV-2, respectively. The interval between disease onset and diagnosis was 8.5 days (IQR, [4-11]). With the deterioration of disease, most patients experienced consecutive changes in biochemical parameters, including lymphopenia, leukocytosis, thrombocytopenia, hypoproteinemia, as well as elevated D-dimer and procalcitonin. Regarding the immune dysregulation, patients exhibited significantly decreased T lymphocytes in the peripheral blood, including CD3+T, CD3+CD4+Th, and CD3+CD8+Tc cells. By the end of the disease, most patients suffered from severe complications, including ARDS (94.4%), acute cardiac injury (55.6%), acute kidney injury (38.9%), shock (33.3%), gastrointestinal bleeding (5.6%), as well as perforation of intestine (5.6%). All patients died within 45 days after the initial hospital admission, with the median survivor time of 13.5 days (IQR, 8-17). Conclusions. Our data show that patients experienced consecutive changes in biochemical and immune parameters with the deterioration of the disease, indicating the necessity of early intervention.